Dance Performance | Maria Trika & Tonia Kehagia | TEDxUniversityoftheAegean (TEDx UniversityoftheAegean, 2020)
: Υπότιτλοι AUTHORWAVE Παρακαλώ, Υπότιτλοι. Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE But I will be afraid Of being marked as much as I know And i do not want to be afraid Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου, η καρδιά μου. Αυτή είναι η καρδιά μου. I'm under your spell Ain't nobody's business I'm already there It ain't nobody's business Every time he walks out the door I wonder if he's ever coming back I can't help but love the taste of danger, babe And the howl and the wind and the rust in his hands I got caught out in the rain If I die, I don't care, I'm in love I'm in love, I'm in love with this man I got caught out, caught out, caught out in the rain I heard him crying in his sleep last night No man wants to be told that he's been crying When he wakes up I tell him it's gonna be alright But I know that he knows that I'm just lying I heard he shot a man down in the street And he tore his soul apart Last night when he was making love to me There was another woman in his heart I got caught out in the rain If I die, I don't care, I'm in love I'm in love, I'm in love with this man I got caught out, caught out, caught out in the rain In the rain In the rain I got caught out in the rain If I die, I don't care, I'm in love I'm in love, I got caught out, caught out, caught out in the rain In the rain In his night, in his pain In his night Ain't nobody's business Ain't nobody's business Kissing down Like a spell